PENILAIAN ACUAN PATOKAN DALAM EVALUASI PENDIDIKAN ISLAM - Nurmanto, Yusuf; Ashari, Muhammad Yahya (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2023)
Abstract: Islamic education plays an important role in the formation of quality individuals who have positive contributions. The benchmark assessment in evaluating Islamic education aims to determine the effectiveness of Islamic religious education learning outcomes. As well as measuring with certainty the goals and competencies that have been set as success criteria. The Minimum Requirements Criteria is a reference in determining a student's minimum mastery of certain material and is a reference for students to assess the basic abilities they have learned. This research is qualitative research using the research library method by selecting various scientific literature, books, journals and other related sources of information. As well as filtering updated literacy and relevant sources on the topic of discussion. The results of this research are that the success of a student who is able to achieve the criteria of 70% - 80% in his understanding, then in classifying these students can be measured through understanding and through mastery o f the material that has been taught to him and for students who do not reach the specified competency it is necessary to a remedial program is carried out.